LEGALITAS WARIS LINTAS RELIGI PERSPEKTIF YUSUF AL-QARAḌAWĪ DAN ‘ABD ALLĀH AḤMED AL-NA‘ĪM DITINJAU DARI MAQĀṢID SHARĪ‘AH IMAM AL-GHAZĀLĪ: Indonesia - Ramadheni, Shaka Danendra; Sabri, Fahruddin Ali (al-Rasῑkh: Jurnal Hukum Islam, 2024)
Raf‘ al-ḥaraj as an effort to remove hardship from a matter that is considered excessive for the soul, body, or property, either now or in the future. This study emphasizes to find the method of istinbāṭ, the foundation of legal istinbāṭ, and the analysis of the opinion of the legality of cross-religious inheritance of al-Qaraḍawī and al-Na'īm in the corridor of maqāṣid sharī‘ah of Imam al-Ghazālī. This research is a normative legal study with a library research approach to the book Fatwa-Fatwa Kontemporer volume 3 by Yusuf al-Qaraḍawī and the book Dekonstruksi Syari’ah: Wacana Kebebasan Sipil, HAM, dan Hubungan Internasional dalam Islam by ‘Abd Allāh Aḥmed al-Na‘īm. The study found that: first, al-Qaraḍawī uses the legal istinbāṭ approach of qiyās, maṣlaḥah mursalah, and the Hanafi school of thought on the interpretation of the connotation of kafir; while al-Na‘īm chooses to use reverse nasakh. Secondly, state policy and the social context of Muslim minorities influenced al-Qaraḍawī in issuing ijtihad on the legitimacy of inter-religious inheritance, while al-Na‘īm was motivated by the social context of his country and the death of his teacher, Mahmud Taha. In addition, it can be seen that in forming their opinions on the legitimacy of inter-religious inheritance, both figures strongly consider ḥifẓ al-dīn, ḥifẓ al-nafs, and ḥifẓ al-māl. This research is expected to contribute to offering a new perspective on Islamic law in the corridor of societal pluralism through maqāṣid sharī‘ah analysis.